Adolescents' Experiences of Participating in Sensitive Research: A Scoping Review of Qualitative Studies. (July 2023) - Neelakantan, Lakshmi; Fry, Deborah; Florian, Lani; Meinck, Franziska
Despite an increasing emphasis on adolescents' participation rights, there are concerns about their participation in research on sensitive topics, such as trauma and violence. This review reports findings of a scoping review that examined the nature and extent of qualitative studies conducted with adolescents about their experiences of participating in research on sensitive topics. Studies were identified by searching electronic databases and grey literature and reported on qualitative and mixed-methods studies eliciting adolescents' experiences of participating in research on sensitive topics. Seventeen (17) studies were included after screening 4426 records. The scoping review revealed significant adolescent benefits from participation, relating to positive emotions, skill acquisition and enhanced self-efficacy and interpersonal relationships. To a lesser extent, participants also experienced burdens relating to negative emotions, concerns about confidentiality and privacy and inconvenience of participation, which were mitigated by careful attention to research design and researcher engagement and training. Participants shared insights into their motivation to participate, and factors that impacted their experiences of research, such as ethical considerations, including consent procedures, safety and connection in research, study procedures and documentation and researcher characteristics. There were tangible benefits and some burdens involved in adolescents' participation in sensitive research. This review considers implications for research and practice, such as the need to regularly publish findings of consultations, assessing caregiver consent requirements, obtaining adolescent views on study documents and measures and building on existing research, differentiated by age, gender and dis/ability status, especially in diverse and under-represented regions.